Impact Assessment of a Programme on Medication-taking Behaviour and Health Awareness Among Low-income Community in the State of Penang, Malaysia - Radieah, Mohd Nor; Manaf Normaliza, Abdul; Amirah, Mohd Gazzali; Mohamed Azmi, Ahmad Hassali (Journal of Pharmacy Practice and Community Medicine)
The study was conducted by using a validated questionnaire and the respondents chosen are those from lowincome status and relatively low level of education in the State of Penang, Malaysia. A total of 65 respondents were interviewed based on participatory approach with an attempt to capture qualitative information with regards to income status, personal living condition and medication-taking behaviour. Majority of the respondents have a good background on drug information. This is given by the number of patients that understand the importance of drug treatment, although in term of application, problems do arise due to forgetfulness, worries of medication side effects and confusions due to multiple medications. This warrants further education from local pharmacists and a subsequent drug awareness program could be organized to overcome these problems faced by the respondents. The respondents also represented common chronic disease pattern among Malaysian, in which around 30% suffers from cardiovascular-related diseases and more than 20% has diabetes. Indeed, more health-awareness campaign is needed to educate the public on the importance of health and disease prevention. This survey found that the specific community in Penang, Malaysia has benefited from the multiple health-awareness programs organized in their area through improved medication-taking behaviour and health-related knowledge. They are aware on the importance of the medications, although there are some respondents that do not have similar view. However, incompliancy is still a problem. Incompliance will lead to medication wastage which will subsequently affect the overall government cost, the environment and most importantly the patients’ health outcome.
Keywords: Low-income community; Health promotion; Awareness of health